Pyrazine-Based Blue Thermally Activated Delayed Fluorescence Materials: Combine Small Singlet–Triplet Splitting With Large Fluorescence Rate - Liu, Junyuan; Zhou, Keren; Wang, Dan; Deng, Chao; Duan, Ke; Ai, Qi; Zhang, Qisheng (Frontiers in Chemistry, 2019)
Metal-free thermally activated delayed fluorescence (TADF) emitters have emerged as promising candidate materials for highly-efficient and low-cost organic light-emitting diodes (OLEDs). Here, a novel acceptor 2-cyanopyrazine is selected for the construction of blue TADF molecules via computer-assisted molecular design. Both theoretical prediction and experimental photophysical data indicate a small S1-T1 energy gap (ΔEST) and a relative large fluorescence rate (kF) in an o-phenylene-bridged 2-cyanopyrazine/3,6-di-tert-butylcarbazole compound (TCzPZCN). The kF value of 3.7×107 s-1 observed in a TCzPZCN doped film is among the highest in the TADF emitters with a ΔEST smaller than 0.1 eV. Blue TADF emission is observed in a TCzPZCN doped film with a short TADF lifetime of 1.9 μs. The OLEDs using TCzPZCN as emitter exhibit a maximum external quantum efficiency (EQE) of 7.6% with low efficiency roll-off. A sky-blue device containing a derivative of TCzPZCN achieves an improved EQE maximum of 12.2% by suppressing the non-radiative decay at T1.